2021
DOI: 10.3389/fphar.2020.614164
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Dose Optimization of Ganciclovir in Critically Ill Children

Abstract: Objective: The present study aims to establish a population pharmacokinetic model of ganciclovir and optimize the dosing regimen in critically ill children suffering from cytomegalovirus related disease.Methods: A total of 104 children were included in the study. The population pharmacokinetic model was developed using the Phoenix NLME program. The final model was validated by diagnostic plots, nonparametric bootstrap, visual predictive check, and normalized prediction distribution errors. To further evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The intra‐day and inter‐day bias of accuracy was ±6%. The CV and bias values were similar to previously reported values for ganciclovir (Cimoch et al, 1998; Li et al, 2021; Page et al, 1996).…”
Section: Methodssupporting
confidence: 90%
“…The intra‐day and inter‐day bias of accuracy was ±6%. The CV and bias values were similar to previously reported values for ganciclovir (Cimoch et al, 1998; Li et al, 2021; Page et al, 1996).…”
Section: Methodssupporting
confidence: 90%
“…The characteristics of each study are summarized in Table 2 . Twelve of the sixteen studies were prospective [ 8 , 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and four studies were retrospective [ 9 , 10 , 28 , 29 ]. The number of subjects ranged from 8 to 105, with only two studies with less than 10 subjects [ 8 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In many studies, the combination of naproxen and other agents with a typical OCT2 substrate (cimetidine) increased the plasma concentration of cimetidine, thereby separately increasing the toxicity of cimetidine [ 29 ]. Ganciclovir [ 30 ], its pharmacokinetic behavior in some studies [ 31 , 32 ], and part of its MATE1 inhibitors or substrate share, showed no significant change in pharmacokinetics parameters, which may be related to other excretory pathways in the body [ 33 ]. In addition, this paper also examines the ligation of the bilateral renal compensatory, where the transporter will affect the elimination of the substrate, and the results showed that the left kidney transporter expression showed no obvious change.…”
Section: Discussionmentioning
confidence: 99%